(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This study examines the trends in consumer goods production in the Republic of Uzbekistan, including growth dynamics across key sectors and the role of domestic and external demand. The analysis identifies existing challenges related to expanding production capacity and ensuring adequate supply of locally produced goods to the population, and proposes measures to address these issues. Particular emphasis is placed on the adoption of innovative technologies and the increasing contribution of small businesses and private entrepreneurship to sectoral development.